Preliminary Investigation of the Safety of Escalating Cannabinoid Doses in Healthy Dogs - Vaughn, Dana; Kulpa, Justyna; Paulionis, Lina (Frontiers in Veterinary Science, 2020)
Objective: To determine the safety and tolerability of escalating doses of three cannabis oil formulations, containing predominantly CBD, THC, or CBD and THC (1.5:1) versus placebo in dogs. Design: Randomized, placebo-controlled, blinded, parallel study. Animals: Twenty healthy Beagle dogs (10 males, 10 females). Methods: Dogs were randomly assigned to one of five treatment groups (n=4 dogs per group balanced by sex): CBD-predominant oil, THC-predominant oil, CBD/THC-predominant oil (1.5:1), sunflower oil placebo, medium-chain triglyceride oil placebo. Up to ten escalating doses of the oils were planned for administration via oral gavage, with at least three days separating doses. Clinical observations, physical examinations, complete blood counts, clinical chemistry, and plasma cannabinoids were used to assess safety, tolerability, and the occurrence of adverse events (AEs). AEs were rated as mild, moderate, or severe/medically significant. Results: Dose escalation of the CBD-predominant oil formulation was shown to be as safe as placebo and safer than dose escalation of oils containing THC (CBD/THC oil or THC oil). The placebo oils were delivered up to ten escalating volumes, the CBD oil up to the tenth dose (640.5 mg; ~62 mg/kg), the THC oil up to the tenth dose (597.6 mg; ~49 mg/kg), and the CBD/THC oil up to the fifth dose (140.8/96.6 mg CBD/THC; ~13 mg/kg CBD + 9 mg/kg THC). AEs were reported in all dogs across the five groups and the majority (94.9%) were mild. Moderate AEs (4.4% of all AEs) and severe/medically significant AEs (0.8% of all AEs) manifested as constitutional (lethargy, hypothermia) or neurological (ataxia) symptoms and mainly occurred across the two groups receiving oils containing THC (CBD/THC oil or THC oil). Conclusions and clinical significance: Overall, dogs tolerated dose escalation of the CBD oil well, experiencing only mild AEs. The favorable safety profile of ten escalating doses of a CBD oil containing 18.3 to 640.5 mg CBD per dose (~2 mg/kg to ~62 mg/kg) provides comparative evidence that, at our investigated doses, a CBD-predominant oil formulation was safer and more tolerated in dogs than oil formulations containing higher concentrations of THC.